REVIEW: BLACK BONE SYNDROME IN BROILERS - Baldo, G. A. A.; Almeida Paz, I. C. L.; Garcia, E. A.; Amadori, M. S.; Alves, M. C. F.; Molino, A. B.; Vieira Filho, J. A.; Santos, L. S. (Revista Brasileira de Engenharia de Biossistemas, 2014)
Some factors involved in the incidence of black bone syndrome and its consequences on the quality and acceptability of meat from the thighs and drumsticks of broilers are described in this review. It is know that the conservation of thighs and drumsticks by freezing leads to the formation of ice crystals that disrupt the cells of the bone marrow, causing leakage of hemoglobin present in the same, when the bone is brittle or porous sharpens extravasation of blood the occurs primarily in the proximal tibia and the femur. The darkening caused in meat adjacent the bone is called of black bone syndrome and has implications in meat quality, mainly by changing the appearance of the same due to darkening caused. The darkening resulting from extravasated blood in the meat has implications for the quality in the same and can result in problems acceptance of meat from thigh and drumsticks. Thus, it becomes necessary to provision the long term, genetic screening focused on the bone structure and the short term with the addition of nutrients can improve bone quality.